The Benefits and Challenges of the Parental Monitoring of YouTube in Adolescents’ Lives: A Qualitative Study of Emotion and Sleep Regulation - Linda Charmaraman; Ramona Smucker; Sally A. Theran; Srimayee Dam; Jessica Anthony (Behavioral Sciences, 2025)
YouTube is the most popular social media platform for children and adolescents, yet relatively little research has been conducted on adolescents’ use and their motivations for use. Prior research has predominantly focused on measuring the quantity of time spent on the platform, and less is known about the motivations and self-awareness of using YouTube as children turn into tweens and teens. Stemming from a larger survey study of adolescent social technology use, we interviewed a subset of 35 youths (50% female, 49% male, 1% non-binary) to qualitatively explore the benefits and challenges of YouTube use. Thematic analyses revealed the wide range of emotional responses and regulation that were attributed to YouTube use, including humor, fear, anger, insecurity, and anxiety. Some participants experienced wishful identification with YouTube influencers, and others viewed YouTube as entertainment or an escape from boredom. Sleep regulation was mixed, in that for some, YouTube was a distraction from getting enough sleep, and for others, it helped them fall asleep. Parental monitoring was a developmental challenge as the youths described their parents as lacking knowledge about the length of time they spend on the platform and/or the risky YouTube content that they watch, particularly as they got older. These exploratory findings may be pertinent for parents, educators, and clinicians.